Briefwechsel 1907-1925 Vollständige Ausgabe, Band 2 1915-1925 - Freud, Sigmund (Turia und Kant, 2010)
The letters between Sigmund Freud and Karl Abraham constitute one of the most important correspondences of Freud. Karl Abraham was an important and influential early member of Freud's inner circle of trusted colleagues. As such he played a significant part in the establishment of psychoanalysis as a discipline. Regarded by Freud biographer Ernest Jones as one of the best clinical analysts among his contemporaries, he also contributed important elaborations and developments of Freud's theories.In 1965, there appeared a first, censored and incomplete edition of this correspondence. In 2002, a completed edition came out in English translation. The present publication will be the first complete edition of this major correspondence in the original German, All letters, postcards, telegrams, notes, and enclosures that have been preserved and could be found are reprinted without omissions or pseudonyms. Added are both editorial and text-critical footnotes, plus an introduction and an appendix with pertinent additional material.It is now possible to explore first-hand the complex relationship that existed between Freud and his master pupil, and to follow their exchange on theoretical and clinical matters, but also on family members, their various travels, political and historical events, etc., and on their combined and individual relationships with other colleagues, such as C. G. Jung or the members of the so-called Secret Committee around Freud. This substantial and absorbing collection of letters enables the reader to gain valuable insights into these two pioneers of psychoanalysis, into the history of the psychoanalytic movement, and into the development of both Freud's and Abraham's theories.Due to the length of this correspondence (appr. 900 pages in print), this edition will appear in two volumes.